Agrobacterium rhizogenes-mediated transformation of Hypericum sinaicum L. for the development of hairy roots containing hypericin - Heba Desouky Khlifa; Magdalena Klimek-Chodacka; Rafal Baranski; Michal Combik; Hussein Sayed Taha (Universidade de São Paulo, 2020)
Hypericum sinaicum L. is an endangered Egyptian medicinal plant of high importance due to the presence of naphthodianthrones (hypericins), which have photodynamic properties and pharmaceutical potential. We sought to assess H. sinaicum ability to develop hairy roots that could be cultured in contained conditions in vitro and used as a source for hypericin production. We used four A. rhizogenes strains differing in their plasmids and chromosomal backgrounds to inoculate excised H. sinaicum root, stem and leaf explants to induce hairy root development. Additionally, inoculum was applied to shoots held in Rockwool cubes supporting their stand after removal of the root system. All explant types were susceptible to A. rhizogenes although stem explants responded more frequently (over 90%) than other explant types. The A4 and A4T A. rhizogenes strains were highly, and equally effective in hairy root induction on 66-72% of explants while the LBA1334 strain was the most effective in transformation of shoots. Sonication applied to explants during inoculation enhanced the frequency of hairy root development, the most effective was 60 s treatment doubling the percentage of explants with hairy roots. However, shoot transformation was the most effective approach as shoots developed hairy roots within 10 days after inoculation. Molecular analyses confirmed that the established hairy root cultures in vitro were indeed obtained due to a horizontal gene transfer from bacteria. These cultures grew fast and the hypericin content in hairy roots was about two fold higher than in H. sinaicum plants as determined by HPLC.